The Impact of Proactive Human Resource Functions on Sustainability in The Gambia During COVID-19: Organizational Agility as a Mediator - Nugrahanti, Ratri Buda; Armanu, Armanu; Irawanto, Dodi Wirawan; Hadiwidjojo, Djumilah (The Journal of Behavioral Science, 2025)
Background/problem: The reliance on tourism in The Gambia, was disrupted by the COVID-19 pandemic, and revealed critical vulnerabilities in organizational sustainability. While sustainable human resource management (SHRM) aligns human resource (HR) practices with long-term goals, limited research explores its human-centered outcomes. This study addresses the gap in HR management research on the human and social dimensions of sustainability, focusing on how proactive HR functions and organizational agility contribute to SHRM in resource-constrained contexts like The Gambia. Objective/purpose: This research aimed to evaluate the influence of proactive HR functions on SHRM during the COVID-19, with a particular focus on examining the mediating role of organizational agility. Design and Methodology: This study adopted a quantitative approach, utilizing data from 222 directors and managers of private businesses in The Gambia, and applied structural equation modeling for hypotheses testing. Results: The results reveal that proactive HR function has a significant direct effect on sustainable HRM (β = .14, p < .001) and organizational agility (β = .54, p < .001). Additionally, organizational agility demonstrates a strong and significant direct relationship with sustainable HRM (β = .54, p < .001). Furthermore, proactive human resources function indirectly influences sustainable HRM through the mediation of organizational agility (β = .40, p < .001). Conclusion and Implications: This study highlights the critical role of proactive HR functions in fostering SHRM and organizational agility. By integrating resource-based theory, social cognitive theory, and organizational development principles, it is recommended that proactive strategies need to optimize resources, enhance employee behavior, and cultivate adaptability. Hence, this provides insights for building resilient and sustainable organizations.